(untitled) (Research, Society and Development, 2020)
Historically the rural communities of the Brazilian municipalities suffer from the absence, lack of attention and lack of assistance on the part of managers. As a strategy to counter this "Oblivion" and as a consequence of the opening of the popular participation in discussions about public policies towards Brazilian field Municipal Councils were created sustainable Rural Development (CMDRS), in which ends up being a form of rural communities to organize themselves and claim rights. The present study aimed to analyze the contents environmental deterioration of rural areas of the municipality of Pombal-PB in order to assist in the process of knowledge construction rural location within a clipping built space collectively in order to assist local knowledge construction process, subsidizing as well as discussions context Municipal Council of sustainable Rural Development. The present work was carried out in the municipality of Pombal-PB, which lies in the West of the Brazilian State of Paraiba and mesoregion Paraibano. To this end, some search procedures and techniques, were adopted were: 1) Fieldwork with the organs, trade unions and Actors who work directly or indirectly in the planning and management of sustainable Rural Development for the construction of a space base only, built collectively;2)Secondary data research that fueled the system adopted to analyses the sustainability of Rural Pombal; and 3) Office research which resulted in the tabs, data analyses and spatialization. As a result, rural areas that are part of different regions de Pombal are the most problematic in terms environmental, requiring special attention on the part of the actors who work directly or indirectly with sustainable rural development.